967. Safety Outcomes of a Hospital-wide β-Lactam Graded Challenge Allergy Protocol. (15th December 2022) - McGuire, Erin; Wang, Sheila K; Sutton, Sarah; Hoff, Brian M; Zembower, Teresa; Grammer, Leslie; Cyrus, Rachel M; Bertram, Christie M; Rhodes, Nathaniel J; Justin Moore, W; Scheetz, Marc H; Postelnick, Michael
Abstract: Background: Up to 15% of hospitalized patients report a penicillin allergy, but most can tolerate a β-lactam (BL). Use of second-line non-BL antibiotics poses untoward health consequences. Assessing for true penicillin allergies includes penicillin skin testing (PST) and a direct amoxicillin challenge, each with their own limitations in hospitalized patients. For inpatients, a graded challenge (GC) with the desired BL offers a streamlined approach for many who could benefit from a first-line BL agent. In 2019, a hospital-wide BL Allergy Assessment and Clinical Pathway was implemented, including a BL GC protocol for low-risk patients. This study aimed to assess the safety of the GC procedure in hospitalized patients. Methods: A retrospective, observational cohort study of adult inpatients who completed a GC procedure between Sept 2019 – Sept 2021 was conducted. Primary objective: determine the incidence of a significant hypersensitivity reaction from a BL GC. Secondary objectives: 1) determine the incidence of a non-hypersensitivity reaction and 2) identify antimicrobial stewardship interventions in those tolerant to a BL GC (e.g. antibiotic switch to a BL with completion of treatment course and de-labeling of penicillin allergy). Results: Fifty-one patients completed a GC procedure. Most (78%) had a reported allergy to penicillin vs. other BL antibiotics. Reported allergic reactions stratified by risk for a serious hypersensitivity episode were: low/reaction > 10 yrs ago – 33%; moderate-high/reaction > 10 yrs ago – 47%, and moderate-high/reaction < 5 yrs ago – 19.6%. A PST prior to a GC was performed in 75% of patients. Common GC agents included amoxicillin-clavulanate (16%), amoxicillin (12%) and ceftriaxone (12%). One patient experienced a hypersensitivity reaction managed with diphenhydramine and another patient had a non-hypersensitivity reaction. Both cases were non-life-threatening. Of the 49 patients who tolerated a GC, 76% were switched to a BL with completion of treatment course, and 84% of documented penicillin allergies were de-labeled or clarified in the electronic medical record. Conclusion: The GC procedure in our hospitalized patients was generally well tolerated including those with an allergy history concerning for a moderate-high risk hypersensitivity reaction. Disclosures: Nathaniel J. Rhodes, PharmD, MSc, American Academy of Colleges of Pharmacy: Grant/Research Support|Paratek: Grant/Research Support|Third Pole Therapeutics: Advisor/Consultant Marc H. Scheetz, PharmD, MSc, Abbvie: Advisor/Consultant|Allecra: Grant/Research Support|Merck: Advisor/Consultant|Nevakar: Advisor/Consultant|Nevakar: Grant/Research Support|Premier Healthcare Solutions: Honoraria|Spero: Advisor/Consultant|SuperTrans Medical: Advisor/Consultant|SuperTrans Medical: Grant/Research Support|Takeda: Advisor/Consultant|Third Pole Therapeutics: Advisor/Consultant.